NDC Schemes and Heterogeneity in Longevity : Proposals for Redesign - Holzmann, Robert; Alonso-García, Jennifer; Labit-Hardy, Heloise; Villegas, Andrés M. (World Bank, Washington, DC, 2019)
A positive relationship between lifetime income and life expectancy leads to a redistribution mechanism when the average cohort life expectancy is applied for annuity calculation. Such a distortion puts into doubt the main features of the NDC (nonfinancial defined contribution) scheme and calls for alternative designs to compensate for the heterogeneity. This paper explores five key mechanisms of compensation: individualized annuities; individualized contribution rates; a two-tier contribution structure with socialized and individual rates; and two supplementary two-tier approaches to deal with the income distribution tails. Using unique American and British data, the analysis indicates that both individualized annuities and two-tier contribution schemes are feasible and effective and thus promising policy options. A de-pooling by gender will be required, however.